Laboratory Manual: Advanced Materials Laboratory (BSP3452) - Saifful Kamaluddin, Muzakir; Izan Izwan, Misnon (Penerbit UMP, 2017)
The course contains practical, and hands-on approach of learning techniques for synthesis, and quantitative and qualitative characterization of materials as applied in industry. Focus of laboratory activities are microstructure analysis techniques (QA and QC); to establish students’ deductive skill, most experiment involves further analysis and data manipulation of raw data from advance instrumentation techniques, and also collective data approach in determining a particular material property.